Vulnerability assessment of groundwater to contamination using drastic method: Study in Ngemplak, Ngaglik and Sleman Districts of Sleman Regency, Yogyakarta Special Province - M. Widyastuti (Indonesian Journal of Geography, 2004)
This research is based on the assumption that the physical environ-ment may provide some degree of protection to groundwater against the natural and human impacts, especially with regard to contamination entering subsurface environment. Study on groundwater vulnerability to contamination .become important. It can be used as a valuable planning tool to overcome the problem of groundwater quality due to uncontrolled land development and undesirable activities. The aims of this study are : 1) to study the distribution of DRASTIC parameters, which are depth to water table, rainfall, aquifer media, soil media, topography, impact of vadose zone, and conductivity; 2) to analyze the vulnerability of groundwater to contaminationThe stua5, was performed by weighting and rating method of DRASTIC parameters. The degree of groundwater vulnerability to contamination is depicted in DRASTIC Index. DRASTIC Index is determined by overall sum of all multiplication between score and weight number ofeach parameter. Data manipulation and data analysis were all performed using Geographic Information System (Arc/View version 3.2). The vulnerability map of groundwater to contamination has been generated using overlay operation of DRASTIC parameters.The result showed that DRASTIC index varies between 73 to 172 intervals. Hence, the indexes were categorized into five level of groundwater vulnerability, namely invulnerable (73-92), low vulnerable (93-112), moderate vulnerable (113-132), high vulnerable (133-152) and very high vulnerable (153-172). It is found that more than 50 % of the study area is covered by high and very high vulnerability of groundwater to contamination. The vulnerability level and its area as follows : vo• high 92974.63 ha or 28.18%), high (7049.86 ha or 66.79 %), moderate (529.90 ha or 5.02 %). low (0.148 ha or 0.0014 %) and invulnerable (0.003 ha or 0.0003 %).